Thatwir al-Washilah al-Ta'limiyah Li Maddah al-Nahw Bi Istikhdam Barnamaj Powerpoin al-Tafa'uliy - Barnabas, Raden Ahmad; Jubaidah, Siti; Cholisotin, Tutik (Institut Agama Islam Negeri Curup, 2020)
This study aims to determine how well the use of information technology-based learning media. The development of information technology is utilized in all aspects of human life, including education. The learning media that will befocused on being developed is Power Point. Power Point is one of the learning media that is already familiar among educators and students, because of its easy and effective use. The method used in this study is a development method based on the ADDIE Model (Analyze, Design, Development, Implement, and Evaluate) proposed by Dick and Carey, namely research and development carried out in several stages: 1) Analyzing the needs of educators and students 2) Product design, 3) Product development, 4) Product implementation, and 5) Product evaluation. Based on the stages carried out obtained learning media products that are considered feasible and are needed by students after validating and testing the product. The validation of media experts obtained 92%, and material 99%. Meanwhile, based on user ratings obtained by 86%.